Deteksi Kebangkrutan pada Industri Asuransi Syariah di Indonesia - Bakhtiar, Fayakhun; Munir, Misbahul; Qasas, Ahsan Al (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2018)
This study aims to predict the potential bankruptcy of a sharia insurance company. The analysis model used is the modified Altman Z-score analysis model. The Altman Z-score measurement model will be represented by the ratio of the network model to total assets, retained earnings to total assets, earnings before interest to total assets and capital book value to the book value of debt. The results showed that in 2011-2017 5 sharia insurance companies were in a safe zone (not bankrupt), there was only one sharia insurance company in the gray zone.